2012
DOI: 10.1016/j.culher.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of endolithic fungal hyphae on oolitic limestone buildings

Abstract: International audienceThis study presents characterizations of weathering forms of the same oolitic limestone from four quarries and eight monuments exposed on various environmental conditions focusing on the water-proofing effect of endolithic organic matter. Patinas were analyzed by X-ray diffraction (XRD), scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDX), capillarity coefficient through weathered and unweathered sides, gypsum content and porous network morphology by epoxy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Concha-Lozano et al [114], comparing samples from well preserved and deteriorated limestone monuments in Nîmes and from quarries, found that the thick network of endolithic hyphae can act as a barrier increasing waterproofing of the stone and slowing down the sulphate diffusion into the stone. These results are very promising, nevertheless a standardization of water absorption measurements in situ should be necessary as environmental humidity, and consequently water content of lichens, could entail noteworthy variation in the results.…”
Section: Lichens: Bioprotective or Biodeteriorative Effect?mentioning
confidence: 99%
“…Concha-Lozano et al [114], comparing samples from well preserved and deteriorated limestone monuments in Nîmes and from quarries, found that the thick network of endolithic hyphae can act as a barrier increasing waterproofing of the stone and slowing down the sulphate diffusion into the stone. These results are very promising, nevertheless a standardization of water absorption measurements in situ should be necessary as environmental humidity, and consequently water content of lichens, could entail noteworthy variation in the results.…”
Section: Lichens: Bioprotective or Biodeteriorative Effect?mentioning
confidence: 99%
“…A protective effect by fungal hyphae for oolitic limestone buildings has also been noted (Concha-Lozano et al 2011). However, when lichens are removed by mechanical and/or chemical methods, the structural integrity of the substratum can be reduced and is thereby far more vulnerable to weathering (Silver and Wolbers 2004;Tratebas 2004;McIlroy de la Rosa et al 2012a).…”
Section: 6mentioning
confidence: 97%
“…Therefore, replacement materials have to be chosen from commercially available stones. Their required specifications are usually accurate with regard to mechanical and water transfer properties . In practice, the ranges of compatible properties values are usually defined around those of the original stone …”
Section: Introductionmentioning
confidence: 99%